2020
DOI: 10.1371/journal.pone.0231089
|View full text |Cite
|
Sign up to set email alerts
|

Where does a ‘foreign’ accent matter? German, Spanish and Singaporean listeners’ reactions to Dutch-accented English, and standard British and American English accents

Abstract: How well L2 English is understood and how L2 English speakers perceive one another within varying communication contexts has been studied relatively rarely, even though most speakers of English in the world are L2 speakers. In this matched-guise experiment (N = 1699) the effects of L1 and L2 English accents and communication context were tested on speech understandability (intelligibility, comprehensibility, interpretability) and speaker evaluations (status, affect, dynamism). German (N = 617), Spanish (N = 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
(108 reference statements)
2
16
0
Order By: Relevance
“…For the Dutch listeners, our findings provide evidence against the matched interlanguage speech intelligibility benefit, which holds that non-native listeners may find non-native speakers with the same L1 background easier to understand than native speakers (Bent & Bradlow, 2003;Munro et al, 2006;Stibbard & Lee, 2006;Wang, 2007), and as such our findings are in line with other studies showing that the interlanguage speech intelligibility benefit does not always apply (Hayes-Harb et al, 2008;Munro et al, 2006). Our findings do not provide support for the existence of a native speech intelligibility benefit, which entails that native speakers are considered easier to understand than non-native speakers by both native and non-native listeners (see Major et al, 2002Major et al, , 2005, in line with other studies which also show that a native speech intelligibility benefit does not always occur (Nejjari et al, 2012(Nejjari et al, , 2020. The implication for EMI is that actual understanding of a lecture would not appear to be compromised by non-native accentedness either for non-native listeners (with or without the same L1 background as the lecturer) or for native English listeners, which is important given that the main aim of lectures is the transfer of knowledge.…”
Section: Intelligibilitysupporting
confidence: 88%
“…For the Dutch listeners, our findings provide evidence against the matched interlanguage speech intelligibility benefit, which holds that non-native listeners may find non-native speakers with the same L1 background easier to understand than native speakers (Bent & Bradlow, 2003;Munro et al, 2006;Stibbard & Lee, 2006;Wang, 2007), and as such our findings are in line with other studies showing that the interlanguage speech intelligibility benefit does not always apply (Hayes-Harb et al, 2008;Munro et al, 2006). Our findings do not provide support for the existence of a native speech intelligibility benefit, which entails that native speakers are considered easier to understand than non-native speakers by both native and non-native listeners (see Major et al, 2002Major et al, , 2005, in line with other studies which also show that a native speech intelligibility benefit does not always occur (Nejjari et al, 2012(Nejjari et al, , 2020. The implication for EMI is that actual understanding of a lecture would not appear to be compromised by non-native accentedness either for non-native listeners (with or without the same L1 background as the lecturer) or for native English listeners, which is important given that the main aim of lectures is the transfer of knowledge.…”
Section: Intelligibilitysupporting
confidence: 88%
“…Nejjari et al, 2012;Cargile, 1997;Dalton-Puffer et al, 1997;He & Zhang, 2010;Hendriks et al, 2016;Lindemann, 2003;Matsuura et al, 1994;McKenzie, 2008;Ryan & Bulik, 1982). In line with other research, our results showed that an L2 accent does not necessarily evoke lower affect (Nejjari et al, 2012;Hendriks et al, 2016) or dynamism (Nejjari et al, 2020), and that speaker evaluations can be impacted by context (Cargile, 1997).…”
Section: Speaker Evaluations Accent Context (Rq2)supporting
confidence: 91%
“…This difference was not a surprising response since the practice of face-to-face teaching remains the norm at Chinese campuses ( 42 ). In addition, differences in accent can also add a layer of difficulties when staff from the Australian university are themselves from an EAL background ( 65 – 67 ).…”
Section: Discussionmentioning
confidence: 99%